2018
DOI: 10.25165/j.ijabe.20181103.4249
|View full text |Cite
|
Sign up to set email alerts
|

Review of precision rice hill-drop drilling technology and machine for paddy

Abstract: Mechanized rice direct seeding is a cost-effective and efficient approach for rice cultivation. Recently, the use of rice direct seeding has been increasing rapidly owing to rural labour shortages and continuous increases in agricultural production costs. This article reviews the research and application progress of mechanized rice direct seeding including direct seeding technologies, precision rice seeding, precision rice seed-metering devices, key supporting agronomy technologies for mechanized rice direct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 53 publications
0
31
0
1
Order By: Relevance
“…Selain itu penggunaan traktor telah dapat menghemat penggunaan tenaga kerja yang dapat mempercepat kegiatan persiapan lahan, karena ketersediaan tenaga kerja yang semakin berkurang dan petani dapat melakukan penanaman tepat waktu pada musim tanam. Penerapan mekanisasi pertanian dalam jangka panjang akan mempengaruhi permintaan tenaga kerja manusia, meningkatkan efisiensi tenaga kerja manusia, serta meningkatkan kuantitas dan kualitas hasil produksi pertanian (Zhang, et al, 2018), (Fulin, Shengxue, & Xiaoming, 2016), (Yinggang, et al, 2013).…”
Section: Pengaruh Penggunaan Traktor Terhadap Penggunaan Tenaga Kerja Pada Usahatani Padiunclassified
“…Selain itu penggunaan traktor telah dapat menghemat penggunaan tenaga kerja yang dapat mempercepat kegiatan persiapan lahan, karena ketersediaan tenaga kerja yang semakin berkurang dan petani dapat melakukan penanaman tepat waktu pada musim tanam. Penerapan mekanisasi pertanian dalam jangka panjang akan mempengaruhi permintaan tenaga kerja manusia, meningkatkan efisiensi tenaga kerja manusia, serta meningkatkan kuantitas dan kualitas hasil produksi pertanian (Zhang, et al, 2018), (Fulin, Shengxue, & Xiaoming, 2016), (Yinggang, et al, 2013).…”
Section: Pengaruh Penggunaan Traktor Terhadap Penggunaan Tenaga Kerja Pada Usahatani Padiunclassified
“…This precision seeding system may either be mechanical or pneumatic. Seed spacing uniformity is an important indicator in evaluating seed drill performance because a uniform distribution of seeds can not only provide maximum space for each plant but also make for uniform root size, which can increase yields and reduce harvest loss [4,5] . Thus, productivity depends on the spatial distribution of plants in the crop field.…”
Section: Introduction 1mentioning
confidence: 99%
“…Various studies were conducted to design and evaluate the performance of the pneumatic planting system [4][5][6][11][12][13][14][15][16][17][18] . Yang et al [3] reviewed the research progress and development of precision maize planters and concluded that the usage, modification and improvement in the pneumatic planter depended upon the geophysical and climatic crop requirements.…”
Section: Introduction 1mentioning
confidence: 99%
“…Studies reported that the mechanical, pneumatic and magnetic seed-metering devices are the most common apparatuses for plug tray seeding [4][5][6] . As for a mechanical seed-metering device, seeds' filling, holding and discharging processes are completed by the seeds' gravity and mechanical device [7][8][9] .…”
Section: Introduction mentioning
confidence: 99%